The AGP model for risk management in agile I.T. projects - Sanjeet Singh; Geetika Madaan; Amrinder Singh; Kiran Sood; Simon Grima; Ramona Rupeika-Apoga (Journal of Risk and Financial Management, 2023)
The vast majority of articles on risk in agile-managed projects fail to adequately address the interplay between the agile methodology, the risk management process, and the elements that ultimately determine the success or failure of the project. Too frequently, processes and models are given undue priority over the human element. The aim of this article is to create a risk management model for agile I.T. projects (AGP model). The study sample consists of 1868 valid survey responses from European and Asian countries received between February 2022 and January 2023. We subjected the data to Exploratory Factor Analysis (EFA) and Cronbach's alpha to identify four key factors for dealing with risks in I.T. projects and create the AGP model. The proposed AGP model outlines up to 76% variability in the potential risks that could arise during an I.T. project's deployment. The findings of this study are critical for project managers, I.T. professionals, developers, and system architects involved in I.T. projects. Other stakeholders may be interested in understanding the risks associated with the project and developing strategies to mitigate these risks.
Keywords: 650; agile; information technology; project management; risk; risk management model